Frances Luttikhuizen. Underground Protestantism in Sixteenth Century Spain. A Much Ignored Side of Spanish History - Ignacio J. García Pinilla (Universitat de Girona; Universitat Autònoma de Barcelona, 2018)
Frances Luttikhuizen Underground Protestantism in Sixteenth Century Spain. A Much Ignored Side of Spanish History Göttingen, Vandenhoeck & Ruprecht GmbH & Co. KG, 2017, 435 p. ISBN 9783525551103 (E-Book: 9783647551104)